The future of professional football: A Delphi-based perspective of German experts on probable versus surprising scenarios - Merkel, S.; Schmidt, S. L.; Schreyer, D. (Sport, Business and Management, 2016)
Purpose: - The purpose of this paper is to explore the future of professional soccer by 2025. Scientific foresight studies on this industry do not yet exist despite its current position at a crossroads: toward further exploitation of profit potential? Or clear commitment to the traditional European Model of Sport?